2021
DOI: 10.3390/ma14195715
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Aging of Styrene-Butadiene-Styrene Modified Asphalt Binder with Different Polymer Additives

Abstract: A wide variety of polymer additives have been widely used in recent years. However, the effect of different polymer additives on the durability of asphalt binders has not been investigated thoroughly. To evaluate the aging property of styrene-butadiene-styrene (SBS) asphalt binder with different polymer additives, three polymer modifiers, namely high modulus modifier (HMM), anti-rutting agent (ARA), and high viscosity modifier (HVM), were added to it. First, the Thin Film Over Test (TFOT) and Pressure Aging Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The close physical properties of the four AW powder, such as particle size and density, indicates that the addition of AW did not alter the molecular properties of SBSMA. Hence, the spectra of the modified asphalt binders are very similar to the original SBSMA binder [ 57 59 ]. In addition, no new characteristic absorption peak appeared.…”
Section: Resultsmentioning
confidence: 99%
“…The close physical properties of the four AW powder, such as particle size and density, indicates that the addition of AW did not alter the molecular properties of SBSMA. Hence, the spectra of the modified asphalt binders are very similar to the original SBSMA binder [ 57 59 ]. In addition, no new characteristic absorption peak appeared.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al tested the dynamic modulus of HMAM prepared from low-grade asphalt with different reclaimed asphalt pavement (RAP) contents and found that HMAM with 40% content of RAP had the best modulus properties [25]. The mechanical properties of additive-based HMAM were also evaluated using the dynamic modulus index in studies by Ma [2], Xiao [26,27], Moghaddam [28], and other scholars, and it was found that the dynamic modulus of HMAM with high = modulus agent particles showed a large increase compared to SBS = modified asphalt and normal asphalt mixtures, and the increase in modulus was related to the additive brand, with the average value around 16 GPa [1,[29][30][31]. It can be seen that existing studies have only used the dynamic modulus for the evaluation of HMAM modulus performance, and the correlation between road performance and dynamic modulus of HMAM has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Complete states of knowledge that are useful as background can be consulted in [1,4,[7][8][9]. A great portion of these studies have focused on modifying or improving asphalt binder properties (using polymers, additives, and rejuvenating agents of adherence enhancers, among others) [10][11][12][13]. On several occasions, some of these studies forget that HMAs are materials, whose properties depend on the interaction between asphalt binder-aggregate.…”
Section: Introductionmentioning
confidence: 99%